Evaluation and estimation of changes in water quality using zoning map and researchers-developed software (case study: Pir-Bazar river) - Majid Homami; Seyed Ahmad Mirbagheri; Seyed Mehdi Borghei; Madjid Abbaspour (علوم محیطی)
Introduction: Rivers are among the major water resources and important and vulnerable inland ecosystems (Hayatolgheib et al., 2016). Today, the quality of such water resources has been threatened due to the irregular consumption of water and pollution of rivers by unnatural and human resources (Li et al., 2009). The Peer-bazar River and Anzali International Wetland has been subjected to severe eutrophication  over the past two decades (Zebardast and Jafari, 2014). As a reuslt evaluation and estimation of changes in water quality the mouth area of the main feeding river  estuary in the Anzali wetland (the Peer-bazar River) is in the first priority. Materials and methods: The present study aimed at evaluating the eutrophication status and prediction of temporal-spatial changes in nutrients concentrations, such as ammonium-nitrogen (N-NH3), nitrate (N-NO3), total nitrogen (TN), phosphorous (PO4-3), TP, in the estuary of Pir-Bazar river as the main and most important stream feeding the Anzali International Wetland. Sampling was performed from 10 points of the drainage basin within 18 months from December 2014 to June 2016. In this research, zoning maps were prepared and the status of present and future water quality parameters of the basin were accurately estimated using a researchers software-developed application and the five interpolation methods of Kriging, S-PLUS, polynomial regression, inverse distance to power, and local polynomial; and finally the optimal method was selected through a root-mean-square error (RMSE) based cross validation approach. Result and discussion: The results showed that in this drainage basin, the second order quadratic polynomial regression (with a mean RMSE of 0.2075 for TN and of 0.1475 for TP) and the topical polynomial with power of 10 (order of 3) (with a mean RMSE of 0.331 for TN and of 0.22 for TP) were the best and the worst methods for estimation of nitrate and phosphate levels in the drainage basin, respectively, as compared to other methods. In order to prepare the zoning map, monthly and seasonal maps of spatial distribution of nitrate and phosphate concentrations were created, and temporal (seasonal) changes in nutrients at the wetland entrance (estuary of Pir-Bazar river) were expressed. The results showed that the mean levels of nutrients in Pir-Bazar river water (0.616 mg/L for TN and 0.325 mg/L for TP) were higher than the allowed limits, according to the European directive 80/778/EEC and the OECD standard, (in normal conditions, the limits are 0.1-0.5 mg/L for TN and 0.01-0.1 mg/L for TP in fresh water). Also, according to the results of software, the mean TN to TP ratio at the wetland entrance was maximally 33.7 that exceeded the limit of 16. Therefore, the region’s water is subject to an advanced and critical eutrophication. Considering the positive and high values of the coefficient of performance for TP and TN between 0.87 and 0.918 (mean 0.894), it can be argued that phosphorus and nitrogen in this water basin are likely to share the same source; meanwhile the coefficient of performance varied between 0.187 and 0.721, showing the best performance for nitrate and phosphate, respectively. Conclusion: The results predicted by this software show that the mean annual concentration of ammonium, nitrate, nitrite, phosphate, and dissolved salts in this river will increase about 1.2%, 3.2%, 32%, 5%, and 7%, compared to the current situation in 2020. These figures will be about 3.4%, 9%, 87%, 14%, and 16.5% in 2030; this is a new finding and a reliable innovation in water quality management in the wetland.